CARIES REMINERALIZATION THERAPY – AN IN VITRO EVALUATION OF THE EFFICACY OF THREE REMINERALIZING AGENTS BY SEM AND EDS ANALYSIS - Geeta IB; Pranjul Sharma; Rayala Lokesh; Urvashi Patel (Journal of Ayurvedic Herbal and Integrative Medicine, 2026)
Dental caries, by definition, is one of the most common diseases worldwide. It is dependent on biofilm, diet, and other factors. It causes mineral loss, disrupting the balance between demineralization and remineralization. This has led to the development of various treatment approaches for initial carious lesions. Remineralization requires a natural pathway to restore the mineral loss of hydroxyapatite (HAP) crystals. Many materials have been clinically evaluated and have demonstrated promising results.